Tourniquet-related complications in extremity injuries: a scoping review of the literature - Anaida Xacur-Trabulce; Gessner Casas-Fuentes; Veronica Ruiz-Vasconcelos; Marianne Marchini Reitz; Sharon M. Henry; Thomas M. Scalea; Marcelo A. F. Ribeiro Jr. (World Journal of Emergency Surgery)
Abstract Background Tourniquets are crucial for controlling life-threatening hemorrhage and, therefore, in preventing avoidable deaths in both military and civilian settings. Its increased use since the launch of the Stop the Bleed campaign, however, has raised concerns regarding possible complications associated with its application, including limb ischemia and amputation. The objective of this study was to synthesize the existing evidence regarding complications associated with the use of tourniquets for extremity injuries and identify gaps in knowledge to guide future research on this topic. Methods A review of the literature between 2016 and 2024 was performed including open access retrospective studies, case series, clinical cases, and systematic reviews that addressed tourniquet use in a civilian or military setting in patients with extremity injuries, following the PRISMA-ScR 2018 checklist. PubMed, ScienceDirect, and Cochrane databases were queried, identifying 1,398 articles on the use of extremity tourniquets in military and civilian contexts, focusing on complications. Of these, 1,343 articles were excluded due to duplication or irrelevance based on the title. From the 55 remaining, 37 were excluded after abstract review for not meeting inclusion criteria. Of the 18 full-text articles reviewed, 10 were excluded due to insufficient data, leaving 8 studies for detailed analysis. Results Prolonged application in emergency situations may lead to severe complications, such as nerve injuries, post-tourniquet syndrome and thromboembolic event risks. Nerve palsy has been identified as the most prevalent complication associated with prolonged tourniquet use. Conclusion Improved training is essential to help providers accurately assess bleeding severity and apply appropriate interventions, reducing complications and enhancing outcomes. Future research opportunities should consider: (1) prospective interventional randomized controlled studies aiming to compare the use of tourniquets to different methods of hemorrhage control; (2) development and validation of easy-to-use scores predicting complications and the need of amputation in both civilian and military settings including upper and lower extremities, to better guide clinical decisions and future guidelines; (3) development of better ways to teach lay providers to recognize life threatening bleeding; and (4) development of guidelines for timing of tourniquet loosening, removal or conversion.